A Plasma Proteomic Approach in Rett Syndrome: Classical versus Preserved Speech Variant. (12th November 2013) - Cortelazzo, Alessio; Guerranti, Roberto; De Felice, Claudio; Signorini, Cinzia; Leoncini, Silvia; Pecorelli, Alessandra; Landi, Claudia; Bini, Luca; Montomoli, Barbara; Sticozzi, Claudia; Ciccoli, Lucia; Valacchi, Giuseppe; et al.
Abstract : Rett syndrome (RTT) is a progressive neurodevelopmental disorder mainly caused by mutations in the gene encoding the methyl-CpG-binding protein 2 (MeCP2). Although over 200 mutations types have been identified so far, nine of which the most frequent ones. A wide phenotypical heterogeneity is a well-known feature of the disease, with different clinical presentations, including the classical form and the preserved speech variant (PSV). Aim of the study was to unveil possible relationships between plasma proteome and phenotypic expression in two cases of familial RTT represented by two pairs of sisters, harbor the same MECP2 gene mutation while being dramatically discrepant in phenotype, that is, classical RTT versus PSV. Plasma proteome was analysed by 2-DE/MALDI-TOF MS. A significant overexpression of six proteins in the classical sisters was detected as compared to the PSV siblings. A total of five out of six (i.e., 83.3%) of the overexpressed proteins were well-known acute phase response (APR) proteins, including alpha-1-microglobulin, haptoglobin, fibrinogen beta chain, alpha-1-antitrypsin, and complement C3. Therefore, the examined RTT siblings pairs proved to be an important benchmark model to test the molecular basis of phenotypical expression variability and to identify potential therapeutic targets of the disease.